Salts induced piezoelectric effect in electrospun PVDF based nanohybrids for efficient energy harvesting - Tiwari S.; Maiti P. (My University, 2025)
Polymer-based nanofibers have been pioneering materials for energy harvesting applications. Addition of nanoparticles or salts induce a polar phase to the materials, which enhances the applicability of the material. Salts based PVDF nanofibers have been prepared through an electrospinning process for energy harvesting applications. Incorporation of the metal-salts to the PVDF matrix leads to a better electrostatic interaction which results in better quality beadless fibers. The changes in the structural and thermal properties suggest the transformation of the non-polar phase to an electroactive phase. The increase in the content of the piezo-active phase with the addition of the metal-salts (93%) as compared to pristine PVDF (74%) provides a path for the prepared material to be used in piezoelectric energy harvesting applications. The device fabricated from the electrospun scaffold was subjected to external stress to examine the efficacy of the prepared material. The maximum output voltage generated from finger tapping for P-Li is around 42 V which is much higher as compared to that for the pristine PVDF nanofiber (19.8 V). The piezoelectric coefficient (d33) and maximum output current obtained for the Li-based PVDF nanohybrid are around 27 pC/N and 2.7 μA, respectively, which are considerably higher than the corresponding values for the PVDF fibers (6 pC/N and 0.07 μA). The charging–discharging capability of the prepared device and the electromechanical responses against different modes of external stress application provide further evidence for the prepared hybrid material to act as a potential self-powered piezoelectric energy harvester. © 2023 Elsevier B.V.